Quantification of chromogranin A using a surface plasmon resonance-based biosensor. Issue 34 (11th August 2021) - Xiao, Yang; Tai, Yang; Quan, Xin; Zhao, Chong; Liu, Rui; Tong, Huan; Huang, Zhiyin; Tang, Chengwei; Gao, Jinhang
Abstract : The SPR-based method quantifies CgA with detection range of 0.2–187 ng mL −1, covers the range of most diseases. Abstract : The chromogranin A (CgA) level in the blood is an important biomarker for neuroendocrine tumors and other diseases. Traditional methods for detecting CgA are expensive and time-consuming with low reproducibility. In this study, surface plasmon resonance (SPR), a simple and label-free technique, was validated for quantifying CgA. CgA antibody (CgA-Ab) was immobilized on the CM5 sensor chip (CgA-Ab-CM5) at optimal conditions (pH 5.0, 10 μg mL −1 ). Next, different concentrations of CgA were measured by CgA-Ab-CM5. The binding and regeneration conditions were optimized and used in each measurement. A binding time of 240 s, and flow rate of 30 μL min −1 were chosen as the optimal binding conditions. A pH of 1.75 was the optimal regeneration condition. Compared to the detection range of 23.4–187 ng mL −1 for enzyme-linked immunosorbent assay (ELISA), a linear range of 0.2–187 ng mL −1 was detected based on the response unit (RU), showing high sensitivity and reliability of SPR. Finally, the reproducibility of the CgA-Ab-CM5 chip was accessed by consecutive binding-regeneration cycles for 300 times. In conclusion, the SPR-based CgA-Ab-CM5 chip is a sensitive and reproducible method for quantifying CgA levels in a real-time manner.